PENGARUH PELATIHAN ON THE JOB DAN OFF THE JOB TERHADAP KINERJA STAFF PERAWAT RUMAH SAKIT MUHAMMADIYAH GRESIK - Chusnul Chotimah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2017)
This study aimed to investigate the effect of partially and simultaneously between training on the job and off the job simultaneously affect the performance of staff nurse Muhammadiyah Gresik Hospital. This research was carried out on staff Muhammadiyah Gresik Hospital Nurses as many as 34 people in the sample. The sampling technique was purposive sampling. Data collection instrument used in this study was a questionnaire. The data have been collected and processed using SPSS computing, prior to analysis by multiple linear regression techniques performed classical assumption. Regression analysis showed that the Training On The Job And Off The Job Of Staff Nurse Performance Muhammadiyah Gresik Hospital obtained the equation Y = 0.132 + 0.491 X1 + 0.456 X2. The analysis showed that both variables simultaneously affect the performance of Muhammadiyah Hospital Staff Nurses Gresik is indicated by a value of F calculated (45.328) > F table (3.3).While partially obtained t value for X1 (On the Job Training) is 2.755 and t value for X2 (Off The Job Training) is greater than the 2,551 t table (2.0395). From the evidence, we can conclude that the two variables have a positive effect on the performance of Muhammadiyah Hospital Staff Nurses Gresik. The amount of Adjusted R Square of 72.9 % was obtained , indicating that this variable variable training on the job and off the job can be an impact on staff nurse performance variables while the remaining 27.1 % were caused by other factors that do not exist in this model.